Trustworthiness as information: Satisfying the understanding condition of valid consent - Martin, Robert K. (Bioethics, 2023)
Within medical ethics, there is widespread agreement that morally valid consent includes an understanding condition. Disagreement centers on what is meant by that understanding condition. Tom Dougherty proposed that this understanding condition should be divided into the two mutually exclusive categories of descriptive information and contextual information. Further, Dougherty argues that each type of information is necessary to satisfy the understanding condition. In contrast, I argue that when the deontic aspect of valid consent is in view, each type of information can be sufficient to satisfy the understanding condition on its own. Moreover, by analyzing delegation, which is conceptually related to consent since both are morally transformative actions, I show that delegation often depends not on descriptive or contextual information but on trust. So, I argue that trustworthiness can also be a type of information that does the same work as descriptive and contextual information in satisfying the understanding condition for valid consent.